Comparing Clinical Outcomes on Oncology Patients With Severe Aortic Stenosis Undergoing Transcatheter Aortic Valve Implantation: A Systematic Review and Meta-Analysis - Song, Yumeng; Wang, Yutong; Wang, Zuoxiang; Xu, Chang; Dou, Jingshen; Jiang, Tingbo (Frontiers in Cardiovascular Medicine, 2022)
Objective To compare the clinical outcomes of cancer and no cancer patients with severe AS after TAVI. Methods A computer-based search in PubMed, EMbase, The Cochrane Library, CBM, CNKI and Wanfang databases from their date of inception to Oct. 2021, together with reference screening, was performed to identify eligible clinical trials. Two reviewers independently screened the articles, extracted data, and evaluated their quality. RevMan 5.3 and Stata 12.0 softwares were used for meta-analysis. Results The selected 11 cohort studies contained 182645 patients, including 36283 of cancer patients and 146362 of no cancer patients. The results of meta-analysis showed that the 30-day mortality [OR=0.68, 95%CI(0.63,0.73), I2=0, P＜0.00001] of patients in cancer with AS group was lower than those in no cancer group; 1-year mortality ［OR=1.45, 95%CI( 1.26,1.66), I2=58%, P＜0.00001］and late mortality［OR=1.50, 95%CI(1.34,1.68), I2=55%, P＜0.0001］of patients in cancer with AS group were higher than those in no cancer group. The results of meta-analysis showed that the stroke[OR=0.77，95%CI（0.72,0.82），I2=0，P＜0.00001] and the acute kidney injury［OR=0.78，95%CI(0.68,0.90），I2=77%，P=0.0005］of patients in cancer with AS group were lower than those in no cancer group. The results of meta-analysis showed that no statistical difference was found in cardiovascular mortality, bleeding events, myocardial infarction, vascular complication, new permanent pacemaker implantation and device success rate. Conclusion It is more effective and safer in cancer patients with severe AS who were undergoing TAVI. However, compared with no cancer patients, it is still high in long term mortality, and further study of the role of TAVI in cancer patients with AS is necessary.